Stephen Parker. Bertolt Brecht: A Literary Life. London: Bloomsbury, 2014. x + 704 pp. - Jesse C Wood (Studies in 20th & 21st Century Literature, 2015)
Review of Stephen Parker. Bertolt Brecht: A Literary Life. London: Bloomsbury, 2014. x + 704 pp.
Keywords: Bertolt Brecht; Stephen Parker; Biography; Literary Life; Book Review